"כמו דרך מסננת קרועה": חזרה ויחידאיות ביצירתו של ישיעהו קורן - עמיר אילה (מכאן, 2016)
The article examines the various manifestations of the tension between repetition and singularity in Yeshayahu Koren’s fiction. The three dimensions of this tension correspond to the article’s three parts. The first part connects the tension between singularity and repetition to the word-image encounters in Koren’s writing and to two mimetic approaches in modernist fiction. The second part explores the psychic implications of this tension in the time-space experience of Koren’s characters. In the third part, this very tension is presented as an artistic mechanism, which reflects the characters’ efforts to capture reality and endow it with meaning. While considering its local aspects, Koren’s fiction is examined throughout the article in the broader context of modern fiction.